2018
DOI: 10.1002/adfm.201806821
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Massive Encapsulation via Tandem Step Emulsification in Glass

Abstract: Controlled encapsulation is important in pharmaceutics, agriculture, food products, and in emerging materials applications. Microfluidics offers a compelling approach to create controlled emulsions and microcapsules for these applications, but upscaling of this technology for the robust encapsulation of chemically diverse active ingredients is not yet demonstrated. Here, it is shown that microfluidic step emulsification can be exploited in upscaled glass devices to robustly produce monodisperse double emulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…34,35 Recent advances on microfluidic systems have been used for larger-scale production of water-in-oil-in-water emulsions, producing up to ~50 g.h -1 . 36,37 Furthermore, a combination of large-scale production and machine learning can be used to minimise the need for a human operator checking the continuous production. 38,39 Here, the high throughput production of microcapsules using microfluidics for mechanically triggered self-healing in the cementitious matrix was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Recent advances on microfluidic systems have been used for larger-scale production of water-in-oil-in-water emulsions, producing up to ~50 g.h -1 . 36,37 Furthermore, a combination of large-scale production and machine learning can be used to minimise the need for a human operator checking the continuous production. 38,39 Here, the high throughput production of microcapsules using microfluidics for mechanically triggered self-healing in the cementitious matrix was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 1733 cm −1 was due to the carbonyl stretching of C═O bond and the small peak at 2961 cm −1 can be attributed to the CH stretching. The band at 1682 cm −1 may be caused by an aryl derivative, 47,48 for example due to aromatic C═C bending, whereas the peak at 1147 cm −1 was probably due to the COC stretching. Since NOA 81 is a thiolene‐based resin, the band located at 930 cm −1 was assigned to ═CH bending.…”
Section: Resultsmentioning
confidence: 99%
“…10 The droplet size is mainly determined by the microchannel structure, especially the height of the step. 11 Hati et al 12 reduced the difference in droplet size by adding narrowing and bypassing in the step emulsification device, indicating that the reflux of the continuous phase plays an important role in droplet formation. Van Dijke et al 13 confirmed that there is a critical viscosity ratio of the dispersed phase and continuous phase.…”
Section: Introductionmentioning
confidence: 99%